Maverick or Front-runner? Army Modernization in Hungary in the Light of the Other Visegrad Countries - Sándor Gallai; Dániel Gyuriss (Revista UNISCI, 2024)
This article compares Hungary's defence modernisation policy with that of the other Visegrad countries and finds that Poland has invested the most in developing its military capabilities and, together with the Czech Republic, has benefited considerably from rising international demand stimulated by the war. Both combined the purchase of modern equipment with the award of government contracts to local suppliers. Slovakia followed the same pattern, but without significant export capacity. Hungary, on the other hand, was unable to prevent the collapse of its former defence industry. As a result, its current development programme uniquely integrates the goals of army modernisation with the plan for rebuilding the sector, which relies heavily on the participation of large European companies, whose role is less important in the other countries. Two other distinctive features of the Hungarian modernisation policy are its embeddedness in broader economic and regional policies, and the creation of six distinct territorial clusters where the reorganisation of the sector is taking place.